Teologi Pluralisme Dalam Pendidikan Islam Mencermati lmplikasi Pemikiran Nurcholish Madjid - Esha, Muhammad ln'am (ULUL ALBAB Jurnal Studi Islam, 2004)
The phenomena of religious plurality is like two-edge knife. The religious plurality can give advantages or us to help human life achieving the progress because of life dynamics with those differences. But, on the other hand, it can cause big disaster for human life. Of course, we do not wish religious plurality to be a destructive power. An effort to create the awareness of the plurality must be done to make the plurality become stimulant of progress not a destructive power. In this context, the idea proposed by the thinkers of pluralism, such as Farid Essack, or Nur Cholis Madjid, who have tried to propose the idea in the theological context, find its significance.